Building learning partnerships between schools and universities: an example from south-west England. Issue 5 (20th October 2018) - Passy, Rowena; Georgeson, Jan; Gompertz, Beth
ABSTRACT: In this article we examine the efforts of a University in south-west England to develop long-standing relationships with some partnership schools into a richer association modelled on university practice schools. These are used widely in countries such as Finland, Japan and Hungary, and offer trainee teachers high-quality practica with expert teachers while providing opportunities for university staff to keep their practice up to date and to collaborate in school-based research. Using the research approach of 'Appreciative Inquiry', which builds on the strengths of a social system to shape future sustainability and development, we focus on the experience of three partnerships. In each school a University-based Researcher-in-Residence was paired with a partner teacher or senior leader. We draw on the notion of a 'third space' to examine the ways in and the extent to which the partners in each school have created a non-hierarchical space for collaborative working.